Distribution of Human Rotavirus G Types Circulating in Paris, France, during the 1997–1998 Epidemic: High Prevalence of Type G4 - Gault, Elyanne (American Society for Microbiology, 1999)
Group A human rotavirus G genotypes were determined by means of reverse transcription-PCR in 170 stool specimens from children with acute diarrhea admitted to a Paris children’s hospital during a 1-year survey (1997 to 1998). The isolates all belonged to types G1 to G4, with type G4 predominating (60%).